2021
DOI: 10.3389/fchem.2021.733463
|View full text |Cite
|
Sign up to set email alerts
|

Current Progress and Perspectives on Using Gold Compounds for the Modulation of Tumor Cell Metabolism

Abstract: Altered cellular metabolism, which is essential for the growth and survival of tumor cells in a specific microenvironment, is one of the hallmarks of cancer. Among the most significant changes in the metabolic pattern of tumor cells is the shift from oxidative phosphorylation to aerobic glycolysis for glucose utilization. Tumor cells also exhibit changes in patterns of protein and nucleic acid metabolism. Recently, gold compounds have been shown to target several metabolic pathways and a number of metabolites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 96 publications
0
15
0
Order By: Relevance
“…In recent years, several reviews on gold complexes have been reported with regard to different bioactivities such as anticancer bioactivity, immune response, anticancer drug resistance, tumor cell metabolism, and anticancer mechanisms. [27][28][29][30][31] In this review, the recent development of gold-based complexes against various cancers is comprehensively summarized. This review mainly includes the structure, bioactivity, selectivity, and corresponding mechanism of action of novel gold complexes during 2015-2022.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several reviews on gold complexes have been reported with regard to different bioactivities such as anticancer bioactivity, immune response, anticancer drug resistance, tumor cell metabolism, and anticancer mechanisms. [27][28][29][30][31] In this review, the recent development of gold-based complexes against various cancers is comprehensively summarized. This review mainly includes the structure, bioactivity, selectivity, and corresponding mechanism of action of novel gold complexes during 2015-2022.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al, have reported Auranofin’s anticancer activity through inhibition of the expression levels of key proteins in the PI3K/AKT/mammalian target of rapamycin (mTOR) pathway, in non-small lung cancer cells [ 21 ]. This mechanism of Auranofin action reduces cancer cells’ ability to adapt to the hypoxic microenvironment, by altering the expression levels of the hypoxia-inducible factor-1 (HIF-1) [ 22 ]. Inhibitors of the PI3K/AKT/mTOR pathway represent a promising strategy for anticancer therapy; some of these drugs, such as the mTOR inhibitors everolimus and temsirolimus, have been approved for the treatment of breast cancer [ 23 ].…”
Section: Gold(i)-based Drugs In the Treatment Of Breast Cancermentioning
confidence: 99%
“…However, their K b values are lower than the classical intercalator, ethidium bromide (EB), since they have less p-conjugated aromatic area, and the aromatic rings of EB are similar to the rings of the bases in DNA, leading to easier p-p stacking interaction, 10 while the K b value of 2Cip is higher than those of other previously reported metal complexes containing Cip À (Table 3). It is probable that the steric structures of M(Cip) 2 (H 2 O) 2 , 13 [Cu(Cip)(A [1][2][3][4][5] )Cl] 34 and [Cu(Cip) 2 (OH) 2 ] 56 make interaction with DNA difficult. To confirm their DNA-binding behaviors, it was necessary to carry out a M = Mn, Co and Ni.…”
Section: Dna Binding Studiesmentioning
confidence: 99%
“…Complexes with transition metals such as Co(II), Cu(II), Zn(II), Au(I), Au(III), Fe(II), Ni(II), Pd(II) and Ru(II) have been synthesized, and their cytotoxicity toward cancer cells has been investigated. [2][3][4] In the current study, copper was selected since it is an essential trace element in the body that exhibits low toxicity and plays an important role in the immune system and nerve cells. 5 Copper complexes with diverse organic ligands also exhibit a wide spectrum of biological properties such as antibacterial, 6 antifungal, 7 anti-inflammatory 8 and antiviral activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation